Taktik Bertahan Pemuda Minoritas: Perlawanan Diam dan Mimikri Pemuda Aboge di Lembaga Pendidikan - Ardiansyah, Mochammad Zaka (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2020)
This article reveals that in responding to the religious discrimination against them while studying at educational institutions, Aboge youths fight back. Instead of being silent and accepting of being the target of heresy labeling in schools, madrasas, campuses, and pesantren, Aboge youths develop various survival tactics and respond to the issues by engaging in mimicry and silent resistance. First, they perform mimicry in multiple identities, between NU and Aboge. Second, they pretend that they are menstruating to camouflage at pesantren but then secretly praying and starting the Aboge-style Ramadan fast on the next day. Third, they preten to do Sunnah worship to impress the next day they start the “obligatory fast” of Ramadan together with the majority. This paper is based upon a qualitative study employing in-depth interview and places the mimicry of Homi K. Bhabha and James C. Scott's silent resistance as theory, and the post-colonial as an approach. The results of this study founds that young Aboge who studied in the midst of the Muhammadiyah campus, they apparently are not becoming subordinate. They carried out mimicry by taking Muhammadiyah as the ordinate identity and utilizing the in-between space to survive. Apparently, the ordinate created a new space by constructing artificial identity towards the Aboge by defining them as NU community. This working paper produces an important finding in post-colonial studies, namely a third space that is different from the in-between space offered by Homi K. Bhabha. This third space is a new identity space that does not adopt identities of the colonizer nor the colonized, because the Aboge borrowed NU identity to perform mimicry when facing the ordinate.